Effect of Housing First on Suicidal Behaviour: A Randomised Controlled Trial of Homeless Adults with Mental Disorders. (July 2017) - Aquin, Joshua P.; Roos, Leslie E.; Distasio, Jino; Katz, Laurence Y.; Bourque, Jimmy; Bolton, James M.; Bolton, Shay-Lee; Wong, Jacquelyne Y.; Chateau, Dan; Somers, Julian M.; Enns, Murray W.; Hwang, Stephen W.; et al.
Objective: This study attempted to determine if Housing First (HF) decreased suicidal ideation and attempts compared to treatment as usual (TAU) amongst homeless persons with mental disorders, a population with a demonstrably high risk of suicidal behaviour. Method: The At Home/Chez Soi project is an unblinded, randomised control trial conducted across 5 Canadian cities (Vancouver, Winnipeg, Toronto, Montreal, Moncton) from 2009 to 2013. Homeless adults with a diagnosed major mental health disorder were recruited through community agencies and randomised to HF ( n = 1265) and TAU ( n = 990). HF participants were provided with private housing units and received case management support services. TAU participants retained access to existing community supports. Past-month suicidal ideation was measured at baseline and 6, 12, 18, and 21/24 months. A history of suicide attempts was measured at baseline and the 21/24-month follow-up. Results: Compared to baseline, there was an overall trend of decreased past-month suicidal ideation (estimate = –.57, SE = .05, P < 0.001), with no effect of treatment group (i.e., HF vs. TAU; estimate = –.04, SE = .06, P = 0.51). Furthermore, there was no effect of treatment status (estimate = –.10, SE = .16, P = 0.52) on prevalence of suicide attempts (HF = 11.9%, TAU = 10.5%) during the 2-year follow-up period. Conclusion: This study failed to find evidence that HF is superior to TAU in reducing suicidal ideation and attempts. We suggest that HF interventions consider supplemental psychological treatments that have proven efficacy in reducing suicidal behaviour. It remains to be determined what kind of suicide prevention interventions (if any) are specifically effective in further reducing suicidal risk in a housing-first intervention.